Effect of auxin and polyamines on protein contents and peroxidase activity during in vitro culture of taro - Francisco, A. A. [UNESP] (2017)
Taro (Colocasia esculenta Schott (L.)) is an important crop species of tropical and subtropical regions. The main problem encountered in the implementation of taro culture is the lack of disease-free propagation material due to the conventional way of propagation (vegetatively by corms). The present research investigates the effects of polyamines Spermine (Spm) or Spermidine (Spd) and cytokinin 6-benzyladenine (BA) or auxin indole-3-acetic acid (IAA) on the endogenous levels of polyamine, protein and peroxidase (POD) activity during in vitro culture of taro. Polyamines, used with growth regulators IAA and BA, improved protein contents in shoots, while medium with Spm and Spd improved protein contents in roots. The high activity of POD in roots during rooting indicates that POD may be associated with the rooting process on taro cultivated in vitro.